2006
DOI: 10.1111/j.1540-8175.2006.00304.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Patency of Internal Mammary Artery Grafts to the Left Anterior Descending Artery by Transthoracic Doppler Echocardiography

Abstract: The existence of mosaic, retro, or sufficient ante flows strongly indicated the patency of LIMA to the LAD. When symptoms are possible to be derived from the occlusion of CABG to LAD, TTDE is a promising method to examine whether a LIMA to LAD bypass is patent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Recently, some investigators have reported on the use of Doppler ultrasound for postoperative IMA graft surveillance. 7,8,15 These studies have shown consistent results comparing the preoperative and postoperative IMA flow patterns and velocities. 7,15 The postoperative changes demonstrate a change in the Doppler flow pattern from a high to low resistance signal with decrease in PSV and increase in EDV.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Recently, some investigators have reported on the use of Doppler ultrasound for postoperative IMA graft surveillance. 7,8,15 These studies have shown consistent results comparing the preoperative and postoperative IMA flow patterns and velocities. 7,15 The postoperative changes demonstrate a change in the Doppler flow pattern from a high to low resistance signal with decrease in PSV and increase in EDV.…”
Section: Discussionmentioning
confidence: 68%
“…It has been proposed that these findings could be used to develop standardized methodology for long-term postoperative follow-up of IMA grafts with duplex ultrasound. 8…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, postoperative angiography is still the golden standard to assess IMA graft patency but the invasive nature limits its routine use. Other methods were reported over the last years, including intravascular, transthoracic, and supraclavicular duplex ultrasonography, magnetic resonance imaging and multislice computed tomography 4–10 . Nowadays, 64‐multislice computed tomography (MSCT) angiography has potential diagnostic performance in the diagnosis of coronary artery disease and in (symptomatic) patients after bypass surgery.…”
mentioning
confidence: 99%